2021
DOI: 10.1080/13669877.2021.1936611
|View full text |Cite
|
Sign up to set email alerts
|

Risky-choice framing and its null effect on integral emotions

Abstract: The effects of risky-choice framing are well-established and have been demonstrated in several decision contexts. Recent research has pointed to a role for affect and emotions in risky-choice framing, but those findings may have been influenced by carry-over effects due to the use of multiple decision problems. In a one-off decision, the effects of riskychoice framing on affect and emotions remain unclear. This article extends the risky-choice framing literature by using the Emotion-Imbued Choice model to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Their findings revealed that negative emotions (such as fear) influenced risky investment decision-making, resulting in more distorted probabilities weighting when making decisions. In addition, Cheng et al (2022) also found in their empirical study that incidental emotions (such as fear and anger) influence risky investment decisions. Moreover, Arıkan _ Iyilikci and Amado (2018) also revealed in their empirical study that individuals with certainty-associated conditions outperformed individuals with uncertaintyassociated conditions (such as fear or sadness) in a gambling task.…”
Section: Emotion-imbued Choice (Eic) Modelmentioning
confidence: 88%
See 4 more Smart Citations
“…Their findings revealed that negative emotions (such as fear) influenced risky investment decision-making, resulting in more distorted probabilities weighting when making decisions. In addition, Cheng et al (2022) also found in their empirical study that incidental emotions (such as fear and anger) influence risky investment decisions. Moreover, Arıkan _ Iyilikci and Amado (2018) also revealed in their empirical study that individuals with certainty-associated conditions outperformed individuals with uncertaintyassociated conditions (such as fear or sadness) in a gambling task.…”
Section: Emotion-imbued Choice (Eic) Modelmentioning
confidence: 88%
“…EIC model depicts how rational choice inputs, in conjunction with (a) integral emotions arising from past decisions (e.g. past experiences/probabilities), (b) incidental emotions (such as anger, anxiety) and (c) personality traits (such as impulsivity and self-efficacy), affect an individual's decision-making (Cheng et al, 2022;Lerner et al, 2015;Traczyk and Fulawka, 2016;Wyer et al, 2019). In addition, Lerner et al (2015) states that integral emotions are mostly related to an individuals' past experiences/judgements in decision-making, whereas incidental emotions are considered to be induced within an individual without their awareness and has a triggering effect on an individuals' decisionmaking behaviour.…”
Section: Emotion-imbued Choice (Eic) Modelmentioning
confidence: 99%
See 3 more Smart Citations